Tracer study of 2014 to 2018 MaEd graduates of KSU - Saguibo, Jovito E. (KSU Research Journal, 2019)
This study is primarily a tracer study of the Master of Arts in Education covering SY 2014-2018 to identify the graduates' demographic profile. The study found out that graduates have improved their degree of professionalism. The skills, such as communication skills and human relation skills, provided by the university, were much used. The graduates were much satisfied (2.5) with the university's services, human resources, financial resources, physical facilities, partnerships with other agencies. One hundred percent of the respondents identified the Master's degree outcomes were defined as competitive during ranking, more significant job opportunities, developed professional skills and knowledge job satisfaction, job performance, and improved social relationships. The majority (98%) of the respondents were promoted and rated very satisfactory by their employers. Hence, the findings of the study confirm that advanced educational courses have social, professional, economic, and psychological benefits.